The Courtyard in Cairene Traditional Houses; A Territorial Dispute, Game of Spaces Geometry and Light - Sadek Ahmed Saad (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
The courtyard lost its role in contemporary Egyptian architecture. Despite its importance in the family social life, the western model of the villa and townhouse is adopted. The author argues that presenting the courtyard as a climatic solution only is inaccurate in introducing the courtyard to local urbanism. The study adopted qualitative and quantitative approaches, collecting historic courtyards houses in Cairo analyzing their courtyard form, geometry, and introductory spatial sequences. Related literature was reviewed for collecting data and introducing criteria. The study sample analysis proved the strong relationship between the spatial territoriality, the house transition zone, the public right to assert the order of their built environment (through collective deliberation) and other forces, which are of great importance to the courtyard role and meanings.